2022
DOI: 10.1002/ueg2.12196
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonography in inflammatory bowel disease – So far we are?

Abstract: Intestinal ultrasound (IUS) is a non‐invasive and accurate tool to assess inflammatory bowel disease. The ECCO‐ESGAR guideline recommends the use of IUS for the assessment of disease activity and complications in Crohn's disease (CD). In addition, an increasing body of evidence suggests the use of IUS as alternative to colonoscopy in monitoring CD and in assessing disease activity of ulcerative colitis. Early responsiveness of IUS findings by the first weeks of treatment and the advantage to perform the proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Detection of inflammation in the bowel wall has always remained a challenge and there have been contradictory reports. You et al 19 recently studied correlations of SBW with inflammatory markers and suggested that IUS parameters significantly correlated with the inflammatory biomarkers with a better concordance rate in patients with active small bowel disease than in those with other disease locations like large bowel however Christian et al 20 suggested that traditional imaging and serum biomarkers were not reliable parameters to differentiate inflammation from fibrosis and there was a need for a newer approach. Zittan et al 21 also suggested that fecal calprotectin levels correlated only with colonic inflammation and therefore a need for newer bowel inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of inflammation in the bowel wall has always remained a challenge and there have been contradictory reports. You et al 19 recently studied correlations of SBW with inflammatory markers and suggested that IUS parameters significantly correlated with the inflammatory biomarkers with a better concordance rate in patients with active small bowel disease than in those with other disease locations like large bowel however Christian et al 20 suggested that traditional imaging and serum biomarkers were not reliable parameters to differentiate inflammation from fibrosis and there was a need for a newer approach. Zittan et al 21 also suggested that fecal calprotectin levels correlated only with colonic inflammation and therefore a need for newer bowel inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Although guidance on reporting of IUS parameters is now available [ 10 ▪▪ ], and several promising indices have been developed with ever better methodologies, an optimal IUS index to reflect bowel activity is yet to be defined. Rising interest in IUS also creates a demand for a training curriculum [ 11 ]. Knowledge and skills expected from newly certified IUS practitioners has recently been established based on an international, expert consensus [ 42 ▪▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…IUS allows systematic scanning of the entire abdomen: after gaining panoramic view with a lower frequency (1–5 MHz) convex probe to localize pathologic conditions, detailed examination of the bowel wall is performed with higher frequency (4–8 MHz) linear probes providing a five-layer pattern (Table 1 ) [ 2 ▪▪ , 9 ]. A recent ECCO-ESGAR topical review [ 10 ▪▪ ] providing guidance on reporting of IUS parameters [ 2 ▪▪ , 11 ] (Table 2 ) recommends reporting of thickness of the most involved small bowel and/or colonic segment (bowel wall thickness, BWT) with a 3 mm cut-off value indicating mural inflammation, as well as disruptions of bowel wall. Intestinal vascularization should be reported by a semi-quantitative grading based on color Doppler.…”
Section: Technical Aspects Of Intestinal Ultrasoundmentioning
confidence: 99%
“…Hence, non-invasive imaging techniques would be preferred for patient management and therapy decision-making. In particular, diagnostic approaches like magnetic resonance imaging (MRI), computed tomography (CT), ultrasound (US) and nuclear medicine imaging, such as positron emission tomography (PET) and single photon emission tomography (SPECT), allow a non-invasive evaluation of bowel inflammation [ 4 , 5 , 6 ]. IBD is characterized by mucosal inflammation that leads to irreversible gastrointestinal damage, mediated by pro-inflammatory cytokines such as interleukin-12 (IL-12), tumor necrosis factor-α (TNFα), α 4 β 7 integrin as well as immune system cells like T-lymphocytes, regulatory cells or natural killer cells (NK) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%